Remaja Sehat Bebas Anemia dengan identifikasi Kadar Hemoglobin Pada Siswi SMP N 2 Nekamese Kabupaten Kupang Nusa Tengggara Timur - Novita Lada; Jeanita Kaseh; Aldiana Astuti (Jurnal Nusantara Berbakti, 2023)
: The health of adolescents is a valuable asset for the nation's future. They play a crucial role in the continuity of development and progress of the country. Focusing on the health and nutrition of adolescents is key to optimizing Indonesia's demographic dividend potential by 2030. This study aims to conduct Hb level examinations among students of SMPN 2 Nekamese as an initial step in early detection of anemia cases. Additionally, education on a healthy diet rich in iron, vitamins, and essential nutrients is provided to prevent anemia. The method used involves socialization and Hb level examinations using a POCT device. The research results indicate that out of 36 adolescents examined, 5 of them had Hb levels below the normal range (normally 10-15 grams/dL). The conclusion of this study is that students of SMP N. 2 Nekamese have received important information about the significance of health and nutrition, as well as preventive measures against anemia. These efforts involve various stakeholders, including Poltekkes Kemenkes and local health centers, in providing blood supplements and regular health check-ups to support the well-being of a productive and competitive young generation.